Integrative Transcriptomic and Metabolomic Analyses of the Mechanism of Anthocyanin Accumulation and Fruit Coloring in Three Blueberry Varieties of Different Colors - Liwei Chu; Qianhui Du; Aizhen Li; Guiting Liu; Hexin Wang; Qingqing Cui; Zhichao Liu; Haixia Liu; Yani Lu; Yanqiong Deng; Guohui Xu (Horticulturae, 2024)
Blueberries are recognized worldwide as one of the most important healthy foods due to their anthocyanins, which have special antioxidant properties. They have become a highly produced and valuable fruit crop. Most blueberry varieties are rich in anthocyanins, which impart a beautiful blue color; however, there are currently several blueberry varieties with different colors worldwide, and these special-colored varieties are the key to analyzing the coloring mechanism of blueberry fruit. Fruit color could be seen as an important nutritional quality trait in terms of marketing. In this study, a combination of transcriptomic and metabolomic analyses was performed on three representative blueberry varieties (‘Pink Popcorn’, ‘Chandler’, and ‘Black Pearl’) with pink, blue, and black fruits, respectively. The metabolomic results showed that the delphinium pigment is the dominant anthocyanin, which is the prerequisite for the formation of fruit color in blueberries. We identified 18 candidate structural genes in the anthocyanin biosynthesis pathway that were significantly up-regulated during three stages of fruit ripening in ‘Black Pearl’ and ‘Chandler’, but these were not found to be significantly expressed in ‘Pink Popcorn’ after combining the transcriptomic analysis results. The non-expression of the VcANS gene may lead to the pink color of the mature fruit of ‘Pink Popcorn’. The phylogenetic tree, heatmap analysis, and WGCNA analysis identified a candidate transcription factor, VcMYBA, which may regulate the differences between black and blue fruits in blueberries by regulating the expression level of multiple structural genes in the anthocyanin biosynthesis pathway. These results provide new insights into the mechanisms of anthocyanin accumulation and coloration in blueberries during fruit ripening and can help support production practices to improve fruit quality characteristics. The key candidate genes that regulate the fruit color differences among different blueberry varieties have the potential to enhance the antioxidant properties and quality characteristics of blueberries through future genomic editing.